The effect of soil moisture and cabbage amendment on the thermoinactivation of Phytophthora nicotianae - Coelho, L.; Mitchell, D. J.; Chellemi, D. O. (Springer, 2001)
The analysis of the effect of soil water matric potential and temperature regimes on the inactivation of chlamydospores of Phytophthora nicotianae in cabbage amended soils was evaluated using three matric potentials (0, -10, and -30 kPa), temperature regimes of 1.5 h at 44 degreesC, 5 h at 41 degreesC and 8 h at 35 degreesC, or 3 h at 47 degreesC, 5 h at 44 degreesC and 8 h at 35 degreesC, with a baseline temperature of 25 degreesC during the rest of the day. The results indicated that survival of P. nicotianae was lowest in saturated soil; and as temperature increased, survival of the pathogen decreased at all soil water matric potentials evaluated. Cabbage amendments can enhance the effect of the heat treatment, further decreasing the pathogen population. The soil water matric potentials evaluated represent optimum levels for the study of thermal inactivation. However, under field conditions lower potentials may be found. Extending the range of soil water matric potentials and the treatment time would allow better comparisons with the field data. There is a clear indication that one irrigation period prior to solarization would provide enough moisture to inactivate the primary inoculum of P. nicotianae in the top soil under field conditions; however, other factors may affect the effectiveness of solarization, reducing or enhancing its potential.
Keywords: field capacity; non-chemical control